Are Systematic Reviews and Meta-analysis on the Verge of Extinction with the Advent of Artificial intelligence? - Prannoy Paul; Ashok Shyam; Sujit Jos (Journal of Orthopaedic Case Reports)
Conventionally, systematic reviews and meta-analysis constituted the highest level of evidence from medical research. With the introduction of artificial intelligence (AI), rapid analysis of large amounts of medical data and synthesis of useful results are possible in a fraction of the time taken for systemic reviews and meta-analysis by humans. However, it is not without drawbacks. This article discusses the implications of AI in the future of systematic reviews and meta-analysis in the medical literature.